Research on The Influence of Employee Job Satisfaction on Job Performance UPN "Veteran" East Java Employees - Susi Hariyawati; Siti Ning Farida; Ety Dwi Susanti (Nusantara Science and Technology Proceedings)
The advancement of science and technology can have an influence on the progress of a college. employees who have good quality are very important so that the University produces competitive graduates. Employee performance will have an impact on their personal and tertiary work satisfaction. If the level of employment is low, it will also influence the progress of the college where he works. Therefore, it is necessary to do research related to the influence of the job satisfaction of the employees on the work performance of the employees of UPN "Veteran" East Java.This study consists of two variables namely Job Satisfaction and Job Performance employees. Given that employees also contribute in the realization of the purpose of the institution in this case is UPN "Veteran" East Java. Population of all employees UPN "Veteran" East Java. The research methodology used simple regression. The results of this study indicate that employee satisfaction affects consumer satisfaction.